Karakteristik Pempek Dengan Penambahan Karagenan Sebagai Bahan Aditif Untuk Mempertahankan Kekenyalan Selama Proses Penyimpanan Suhu Rendah (Frozen) - Guttifera, Guttifera; Sari, Selly Ratna; Yesi, Desri (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2023)
Pempek has a short shelf life, so many pempek entrepreneurs market it frozen. The freezing process can cause pempek to lose its elasticity and become mushy when re-cooked. The change in texture results in a lack of consumer liking, so it is necessary to add carrageenan additives to overcome this problem. The purpose of this study was to determine the effect of carrageenan on the characteristics of frozen pempek in terms of physical, chemical and microbiological. This study used a non-factorial complete randomized design (CRD) with treatments including the concentration of carrageenan (A): A0 = 0%, A1 = 0.5%, A2 = 1% and A3 = 1.5%. Parameters determined included chemical (moisture and protein content), physical (texture), and microbiological (total plate count). The results showed that the sample formulation A3 (addition of carrageenan 1.5%) produced the highest texture (most chewy) which is 626.82, the lowest TPC and water concentration TPC 3.17 x 105 and 57.63% and protein 14.45. The addition of carrageenan in the manufacture of frozen pempek is able to maintain the chewiness of pempek that has been stored for 4 weeks in frozen storage with a re-cooking process.